THE IMPLEMENTATION OF CONSTRUCTIVISM THEORY TO IMPROVE PAI CLUSTER LEARNING IN MADRASAH ALIYAH ARIFAH, GOWA REGENCY (International Conference on Social and Islamic Studies, 2021)
This study aims to describe the implementation of constructivism theory to improve the learning of the PAI family in Madrasah Aliyah Arifah, Gowa Regency. This research includes qualitative research with the type of field research. The data from this study were obtained through the methods of observation, interviews and documentation. The data analysis technique used is simultaneous data analysis, namely: (1) data reduction; (2) data display (data display); and (3) drawing conclusions or verification. The results showed that the application of constructivism theory in Islamic Religious Education learning to students of Madrasah Aliyah Arifah Gowa in PAI clumps subjects, provided opportunities for students to make meaning of the material taught and contained in textbooks, but also based on books. other supporters. As for the implementation, most of the aspects of constructivism theory that have been applied by teachers in PAI cluster subjects, while there are several other aspects that have not been implemented. So it can be concluded that there is an application of constructivism theory but it is still not fully implemented optimally. This research activity is an inspiration for teachers for teachers to use the principles of constructivism theory in PAI family learning in accordance with the steps in applying the theory so that students will easily understand learning properly and correctly.